Comparison of Methods for Resolving Child Custody Disputes After Parental Divorce - Rezky, Nadia; Sado, Arino Bemi (Fakultas Syariah INSURI Ponorogo, 2024)
This research aims to analyze the comparison of two post-divorce child custody dispute resolution methods (litigation and non-litigation) along with the obstacles and challenges faced in finding a solution. This research is qualitative research with field research methods and data obtained through observation, interviews and documentation. The result is obstacles in resolving child custody disputes through litigation methods in court which require a long time, large costs and are difficult to implement the judge's decision, especially if the child is in the control of the losing party and does not want to hand over the child voluntarily. There are no specific rules regarding the implementation of hadhanah and considering the child's psychology, so that often the judge's decision is an illusory (futile) decision. Meanwhile, the obstacles to the non-litigation method are that it relies heavily on cooperation and awareness of both parties and there is still a lack of access to special services for the general public to carry out mediation without having to go to court. For this reason, it is necessary to increase competence and innovative approaches for professionals involved in resolving child custody disputes, the formation of policies that are oriented towards the interests of children and awareness of parents to prioritize the best interests of children rather than ego alone.